(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This paper provides an analysis of the methods of regeneration of waste oils. To solve the problems of preventing environmental pollution and import-substituting environmentally safe lubricating oils based on local raw materials with the involvement of additives of vegetable origin.